2007
DOI: 10.2136/vzj2006.0188
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on Soil Dielectric Properties Measured at 50 MHz

Abstract: In recent years a number of soil water monitoring instruments have been developed and made commercially available. These instruments generally respond to the complex soil dielectric permittivity and operate at frequencies between 10 and 150 MHz. Although there is some evidence that these instruments are sensitive to temperature change in certain soils, little empirical data exists describing the degree of this sensitivity. We quantified temperature effects on both the real and imaginary components of the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 32 publications
(66 reference statements)
1
65
1
1
Order By: Relevance
“…Seyfried and Grant (2007) reported that temperature responses were both positive and negative for different soils. Figure 4 shows the permittivity traces at soil temperatures of 10 to 50°C for the Ida soil at a constant water content of 0.30 m 3 /m 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Seyfried and Grant (2007) reported that temperature responses were both positive and negative for different soils. Figure 4 shows the permittivity traces at soil temperatures of 10 to 50°C for the Ida soil at a constant water content of 0.30 m 3 /m 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Temperature effects on TDR measurements is well documented, with dielectric permeability of bulk water increasing with temperature (e.g. Seyfried and Grant, 2007; Freidman and Robinson, 2002; Or and Wraith, 1999). Because the dielectric properties of solids and air are significantly less sensitive to temperature changes than water, the mixture of solid, air and water exhibit a temperature dependence similar to (but smaller than) that of free water (Pepin et al , 1995).…”
Section: Observationsmentioning
confidence: 99%
“…Various models have been developed to quantify the change in dielectric in response to temperature changes (e.g. Or and Wraith, 1999; Seyfried and Grant, 2007). As with the dielectric‐temperature relationship, the effects of temperature on electrical resistance has also been extensively documented.…”
Section: Observationsmentioning
confidence: 99%
“…Finally, we measured the apparent soil electrical conductivity of discrete, homogeneous soil horizons (EC s ) to check the consistency with the surface geophysics EC a , since the latter corresponds to a bulk measurement of the soil horizons EC s above the depth of penetration of the geophysical instrument. We measured the real ( r ) and imaginary (ε r ) dimensionless components of the soil complex dielectric permittivity with a portable Stevens Hydra Probe (Seyfried and Murdock, 2004;Seyfried and Grant, 2007) on the AB and C horizons at 10 vertical soil profiles (locations PD1 to PD10, Figure 2.2). EC s (S/m) is related to ε r as following:…”
Section: Soil Analysismentioning
confidence: 99%
“…A correction for temperature effect was considered as suggested by Seyfried and Grant (2007) in order to obtain standardized values of EC s at 25°C. The areas with a ratio of ε r /ε r >2 were identified as affected by soil salinity (Seyfried et al, 2005).…”
Section: Soil Analysismentioning
confidence: 99%